Verticillium dahliae Inoculation and in vitro Propagation Modify the Xylem Microbiome and Disease Reaction to Verticillium Wilt in a Wild Olive Genotype - Anguita-Maeso, Manuel; Trapero-Casas, José Luis; Olivares-García, Concepción; Ruano-Rosa, David; Palomo-Ríos, Elena; Jiménez-Díaz, Rafael M.; Navas-Cortés, Juan A.; Landa, Blanca B. (Frontiers in Plant Science, 2021)
Host resistance is the most practical, long-term and economically efficient control measure for Verticillium wilt in olive caused by the xylem-invading fungus Verticillium dahliae (Vd), and it is at the core of integrated disease management. Plant’s microbiome at the site of infection may have an influence on the host reaction to pathogens; however, the role of xylem microbial communities in the olive resistance to Vd has been overlooked and remain unexplored to date. This research was focused on elucidating whether in vitro olive propagation may alter the diversity and composition of the xylem-inhabiting microbiome and if those changes may modify the resistance response that a wild olive clone shows to the highly virulent defoliating (D) pathotype of Vd. Results indicated that although there were differences in microbial communities among the different propagation methodologies, most substantial changes occurred when plants were inoculated with Vd, regardless whether the infection process took place, with a significant increase in the diversity of bacterial communities when the pathogen was present in the soil. Furthermore, it was noticeable that olive plants multiplied under in vitro conditions developed a susceptible reaction to D Vd, characterized by severe wilting symptoms and 100% vascular infection. Moreover, those in vitro propagated plants showed an altered xylem microbiome with a decrease in total OTU numbers as compared to that of plants multiplied under non-aseptic conditions. Overall, 10 keystone bacterial genera were detected in olive xylem regardless infection by Vd and the propagation procedure of plants (in vitro vs nursery), with Cutibacterium (36.85%), Pseudomonas (20.93%), Anoxybacillus (6.28%), Staphylococcus (4.95%), Methylobacterium-Methylorubrum (3.91%), and Bradyrhizobium (3.54%) being the most abundant. Pseudomonas spp. appeared as the most predominant bacterial group in micropropagated plants and Anoxybacillus appeared as a keystone bacterium in Vd-inoculated plants irrespective of their propagation process. Our results are first to show a breakdown of resistance to Vd in a wild olive that potentially maybe related to a modification of its xylem microbiome, and will help to expand our knowledge of the role of indigenous xylem microbiome on host resistance which can be of use to fight against main vascular diseases of olive.